(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
The method of researching the phytosanitary condition of mulberries. In order to determine the phytosanitary condition of mulberry plantations, the farms where the study was conducted were inspected three times during the growing season each year, namely when the trees leafed out and one month after leafing out. and August-October, monitoring was carried out. Samples of infected plants were taken for laboratory testing. Disease counts and sampling were carried out diagonally, and the number of trees varied depending on the location and size of the mulberry grove.